PROTECTIVE ROLE OF CARNITINE SYNERGIZED WITH VITAMIN E AGAINST ISOPROTERENOL INDUCED CARDIAC INFARCTION IN RATS. - Huwait, Etimad A.; Al-Ghamdi, Maryam A. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The current study aimed to evaluate the role of carnitine in combination with vitamin E in protection against myocardial infarction induced by isoproterenol (ISO) in rats. Materials and Methods: Rats were grouped into 5 (each 10 rats): Group I. Control fed a standard diet. Group III: Rats were injected with vitamin E (100 IU/kg bw, i.p) daily. Group IV: Rats were given carnitine (20 mg/kg bw, i.p) daily .Group V: Rats were injected with both vitamin E (100 IU/kg bw, i.p) and carnitine (20 mg/kg bw, i.p) daily. On 7th, 8th, and 9th day, rats in groups (II-V) were injection i.p with ISO (55mg/kg b.w for successive three days). The treatment with carnitine and vitamin E were continuous for 21 days. Results: Canirine combined with vitamin E significantly increased coronary flow (CF) (P<0.001) in rats injected with ISO. The recovery of rate pressure product (RPP) and left ventricular developed pressure (LVDP) were significantly improved in treated rats in comparison to untreated. The rats administrated with ISO resulted in a significant elevation of serum enzymes (CK-MB and LDH) compared with control group (p<0.001). However, it returned to about normal. ISO administration resulted in a significant elevation in the levels of malondialdehyde (MDA) and nitric oxide (NO) as compared with control (p<0.001) and a significant reduction in the activities of GSPxase and GSRase (p<0.001) compared with control group. The levels of cardiac inflammatory markers interleukine-6 (IL-6) and tumor necrosis factor (TNF- α) were markedly elevated in rats injected with ISO compared with control group. Vitamin E combined with carnitine reversed these effects. However, pretreatment with vitamin E or carnitine or combined together showed a significant reduction in MDA and NO (p<0.001) and a significant elevation in the activities of GSPxase and GSRase (p<0.001) as compared to ISO injected group. The combined effect was more significant than individual ones. Conclusion: Vitamin E combined with carnitine exerts potential protective effect against MI through suppression of inflammatory mediators and enhancement of antioxidant activity.